Valorization of glycerol through the enzymatic synthesis of acylglycerides with high nutritional value - Sanchez, Daniel Alberto (2020)
The production of specific acylglycerides from the selective esterification of glycerol is an attractive alternative for the valorization of this by-product of the biodiesel industry. In this way, products with high added value are generated, increasing the profitability of the overall process and reducing an associated environmental threat. In this work, nutritional and medically interesting glycerides were obtained by enzymatic esterification through a two-stage process. In the first stage, 1,3-dicaprin was obtained by the regioselective esterification of glycerol and capric acid mediated by the commercial biocatalyst Lipozyme RM IM. Under optimal reaction conditions, 73% conversion of fatty acids and 76% selectivity to 1,3-dicaprin was achieved. A new model to explain the participation of lipase in the acyl migration reaction is presented. It evaluates the conditions in the microenvironment of the active site of the enzyme during the formation of the tetrahedral intermediate. In the second stage, the esterification of the sn-2 position of 1,3-dicaprin with palmitic acid was performed using the lipase from Burkholderia cepacia immobilized on chitosan as the biocatalyst. A biocatalyst containing 3 wt % of lipase showed good activity to esterify the sn-2 position of 1,3-dicaprin. A mixture of acylglycerides consisting mainly of capric acid esterified at sn-1 and sn-3, and of palmitic acid at the sn-2 position was obtained as the reaction product. The influence of the biocatalyst mass, the reaction temperature, and the molar ratio of substrates were evaluated for this reaction using a factorial design. Simple models were used to adjust the consumption of reagents and the generation of different products. The reaction product contained between 76% and 90% of acylglycerides with high nutritional value, depending on the reaction conditions.